Quipper School sebagai Media Pembelajaran Bahasa Arab: Pengaruhnya terhadap Motivasi dan Hasil Belajar Siswa di Madrasah Aliyah - Mualim Wijaya; Nabila Nor Amelya; Najihah Abd Wahid (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2026)
The integration of digital technology into language education has become increasingly important in promoting active and student-centred learning. However, Arabic language instruction in many schools continues to face challenges related to low student engagement and unsatisfactory learning outcomes, while evidence on the effectiveness of digital learning platforms in this context remains limited. This study investigates the effectiveness of Quipper School in improving student engagement and learning outcomes in Arabic language instruction. A quantitative One-Group Pretest–Posttest design was employed involving Grade X students at an Islamic Senior High School. Data were collected through achievement tests and a learning motivation questionnaire and analysed using descriptive statistics, normalized gain (N-gain), and a paired-sample t-test. The results demonstrated significant improvements in both learning achievement and motivation. The mean achievement score increased from 28.07 to 73.04, with a moderate normalized gain (N-gain = 0.62), and the difference between pretest and posttest scores was statistically significant (p = 0.001). In addition, 82.86% of students reported increased motivation toward learning Arabic after using Quipper School. The study contributes to the Technology-Enhanced Language Learning (TELL) literature by providing empirical evidence that Quipper School can support more active and learner-centred Arabic instruction. These findings suggest that the platform offers a practical digital approach for improving Arabic language teaching and learning, although further research using controlled and multi-site designs is needed to strengthen the generalisability of the results